How Can Value be Created and Retained in the Operating System Market? - Nunn, J (2012)
This work sets out to examine the role of Microsoft’s and Apple’s operating systems ‘OS’ within the operating system market, the role that the two companies play in the creation of value, and how value is affected by the passage of time. The thesis suggests that a number of factors affect the creation of value within the operating system market. These include the behaviour of both companies in the way they market-brand themselves, their lock-in of certain aspects of the market and the nature of their products. The thesis also notes that when looking at the effects of value over time, the proposed value within the product, created upon purchase, can also change and either increase or decrease.